Phase-interrogated SPR sensing structures based on tapered and tip optrode optical fiber configurations with bimetallic layers. (21st August 2017) - Moayyed, Hamed; Teixeira Leite, Ivo; Coelho, Luis; Luis Santos, Jose; Viegas, Diana
Abstract: This work reports the theoretical investigation of optical fiber surface plasmon resonance sensors incorporating bimetallic layer combinations. Different metals like silver, gold, copper, and aluminum are considered to investigate the refractometric sensing properties of tapered and tip optrode phase-interrogated optical fiber plasmonic sensor structures. It is shown that the gold–silver combination, coupled to a tip optrode layout, is capable of maximizing the resolution and operation range of these sensing structures for environmental refractive index measurement.